2014
DOI: 10.3164/jcbn.13-70
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian green propolis improves immune function in aged mice

Abstract: Aging weakened innate and adaptive immunity both quantitatively and qualitatively. Some components in propolis could stimulate immune function in young animals or cultured immune cells in vitro. Few studies had been carried out in the aged. The present study was to evaluate the effects of Brazilian green propolis supplementation on the immunological parameters in aged mice. Eighty Kunming mice, aged 15–18 months, were randomly assigned to the control and three experimental groups supplemented with different do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
14

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 44 publications
2
46
0
14
Order By: Relevance
“…With regard to the humoral immune response, several authors reported that propolis and its constituents increased antibody production using different models and antigens (Scheller et al ., ; Park et al ., ; Sforcin et al ., ; Chu, ; Fischer et al ., ; Gao et al ., ; Yang et al ., ). These data strongly suggest the adjuvant capacity of propolis in association with vaccines.…”
Section: Biological Propertiesmentioning
confidence: 99%
“…With regard to the humoral immune response, several authors reported that propolis and its constituents increased antibody production using different models and antigens (Scheller et al ., ; Park et al ., ; Sforcin et al ., ; Chu, ; Fischer et al ., ; Gao et al ., ; Yang et al ., ). These data strongly suggest the adjuvant capacity of propolis in association with vaccines.…”
Section: Biological Propertiesmentioning
confidence: 99%
“…Besides these, over 150 constituents, including flavonoids, phenolic acids, esters, terpenoids, steroids, amino acids and cinnamic acid derivatives have been identified (3), and are hence considered as popular pharmacological research material (4). A broad spectrum of biological activities identified in propolis include antitumor (5)(6)(7)(8)(9)(10)(11)(12), anti-inflammatory (13)(14)(15), anti-bacterial (16)(17)(18), anti-viral (16,19,20) and anti-fungal (16) activities. Propolis is used in cosmetic products, such as body lotions, ointments, face creams and in functional food in various forms, such as tablets, capsules, toothpaste and mouthwash preparations (21).…”
Section: Introductionmentioning
confidence: 99%
“…such as limonene, able to work activates macrophages. Several other studies have shown that some ingredients in propolis, such as caffeic acid phenethyl ester, cinnamic acid, and artepillin C, is also able to activate macrophages in vitro and in vivo [23]. Literature data indicate that the essential oil of Eucalyptus globulus, which contains p-cymene, which is a member monoterpene, is also capable of inducing macrophage response [24] and p-cymene can also stimulate phagocytosis by binding to the receptor TLR4 [25].…”
Section: Effects Of Eep On Macrophages Activitiesmentioning
confidence: 99%